(untitled) (Journal of the College of Basic Education, 2024)
The subject of women’s rights is one of the important provisions that were mentioned in all the holy heavenly books, including in the Glorious Qur’an, the Torah and the Gospel, where he spoke about it in several subjects, and there were women who were forbidden to marry a man who were forbidden by all the sacred heavenly laws, including Islam, but in some of its sources there was a difference In prohibiting it. This study aimed to conduct a comparative study of women’s rights in marriage between the Qur’an and the two covenants. The results were through our comparison of them in women’s rights. There are similarities and differences in women’s rights between the three holy books. Marriage: As for the Qur’an, the prohibition of marriage to female writers, and the Torah, the prohibition of marriage to someone other than the Jewish religion, and the Bible, the prohibition of marriage to someone other than Believers, and the similarity of the Qur’an and the Torah in the story of the marriage of Shuaib’s daughter to Moses, peace be upon him, but there were many aspects of difference in women’s rights in marriage between the Qur’an and the two covenants, including: As for the Qur’an, the obligation of marriage, and as for the Bible and the reluctance to marry, and the difference in the prohibition of incest marriage The prohibition of marriage to the adulteress and the adulterer is for believers, but the Torah prohibits the marriage of priests to adulterers and divorced women, and the permissibility of marrying them is for the prophets, peace be upon them, but the Bible commanded to stay away from adultery, and differed in the prohibition of approaching a married woman: the Qur’an prohibits marriage from a married Muslim woman or writers, and the Bible prohibits exchange Wives and share with others, sanctity Marriage in the presence of religious differences: The Holy Qur’an prohibits marriage to infidels and idolaters, the Torah does not allow marriage when there is a different religious affiliation, the Bible prohibits marriage in the presence of different sects, and the difference in the wives of the prophets, peace be upon them: the Qur’an and the prohibition of marriage to the wives of the Messenger, the Torah and impurity The women of the prophets, the Bible, the mothers and grandmothers of Christ, one of the most famous adulteresses of the advanced era, discontinued marriage: the Qur’an analyzes discontinued marriage and the Bible prohibits it, types of concubines from women: the Qur’an and the permissibility of marriage from cousins, maidservants and the wife of the adopted son, but the Torah and the Bible forbid it, the rule of polygamy: the Qur’an And the permissibility of polygamy to four, with special conditions, the Torah and the Bible, the permissibility of polygamy without restrictions.